Research on the Talent Cultivation Strategy for Enterprise Digitalization Based on New Quality Productivity (Journal of economic and management development research, 2026)
In the era of new quality productivity, the demand for digital talents in enterprises' digital transformation is increasing day by day. However, there is currently a shortage of digital talents, and the training of talents is disconnected from the demands of enterprises. There is a lack of a systematic training system, and the evaluation mechanism needs to be improved urgently, which seriously restricts the digital transformation and development of enterprises. This article analyzes the necessity and challenges of digital talent training in enterprises under the new quality productivity, and proposes three major strategies: "shaping the ecosystem, linking and empowering, and activating the mechanism": First, the government, enterprises and schools should collaborate to optimize the education platform and create a digital talent training ecosystem; second, innovative training models should be adopted to build a "digital + professional" compound talent training program; third, the evaluation system should be improved to establish evaluation indicators centered on digital capabilities.
Keywords: new quality productive forces; enterprise digital transformation; digital talents; talent cultivation strategies